#TITLE_ALTERNATIVE# - Imran (NIM 23496074), Arif
Abstract : Competitive factors of order based manufacturing system are technical ability, price, delivery time and an ability to fulfill delivery time. Determination of delivery time and its fulfillment are influenced by ability for estimating production time when an order is accepted. Determination of production time can be done in two way, namely, based on product (Dimyati et al., 1999) and, based on component (Toha et al 1997a, 1997b). In reality, processing time of an operation can be achieved as a planning period. It is then necessary to develop a model for determining production time based on operation level. Model development is constructed by several phases. The first phase is development of optimization model based on the integer linear programming formulation. The second phase is development of decomposition optimization model based on period. The third phase is development of decomposition model based on a certain period of time and operation in which there are no other operation during that period. Furthermore, the decomposition based on operation and period is carried out at the fifth phase, however if there is capacity left in that period, then the capacity can be used to optimize another operation. Finally, the sixth phase is similar with the fifth stage, but at this stage the product bill of material is involved. The model has been tested on two cases from references. For the first case, the proposed methods give a shorter solution. It is due to the use of difference assumption. On the reference it is assumed that the total time required to meet up each component is similar or less than a period. While in the proposed method it is assumed that total time needed to make up an operation is similar or less than a period. For the second case, even though the reference solution is an optimal solution, the proposed method also gives a shorter solution, which is also caused by the use of difference assumption. On the reference it is presumed that the total time required to meet up a unit product is similar or less than a period.